Pengaruh Aplikasi Pupuk Cair Kompos Rumah Tangga Terhadap Pertumbuhan Dan Hasil Tanaman Gumitir (Tagetes Cerecta) - Lutgardis Erlina Delti; Putu Eka Pasmidi Ariati; Komang Dean Ananda; Putu Laksmi Yuliyanthi Sapanca (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
This research is entitled “ The Effect of Liquid Fertilizer Appilication og Household Waste Compost on the Growth and yield of Gumi. Ttir Jl. Sedap Malam, East Denpasar District. Impementation starst from february 4, 2021 to April 28, 2021. This study aims to determine the effect of giving the best organic loquid fertilizer for the growth og Gumitir flower plants. This study used a Randomized Block Desigen (Rak) with 4 replications and 6 treatmens so that the total number of treatmens was 24 polybags. The treatmen was without fertilizer (control). (k1), liquid organic fertilizer for household waste compost with concentration of water 25 ml/ 1 liter of water (K1), liquid organic fertilizer for household waste compost with concentration of 50 ml / 1 liter air of water (K2), liquid organic fertilizer for household waste compost with concentration of 75 ml/ 1 liter of water (K3), liquid organic fertilizer for household waste compost with concentration of 100 ml/ 1 liter of water (K4), liquid organic fertilizer for household waste compost with concentration of 125 ml/ 1 liter of water (K5). The treatmen with a concentration og 75 ml/ 1 liter of water gave the highest results on the fresh weight parameters of flowers compared to the concentration of 100 ml/ 1 liter og water, 75 ml/ 1 liter of water, 125 ml/ 1 liter air of water, 50 ml/ 1 liter of water, and without fertilizer (control)